Emotions naturally and laboriously expressed: Antecedents, consequences, and the role of valence. Issue 4 (11th January 2020) - Scott, Brent A.; Lennard, Anna C.; Mitchell, Rebecca L.; Johnson, Russell E.
Abstract: The emotion regulation literature has focused primarily on comparing the methods of surface acting and deep acting, yet scholars have also noted the importance of naturally felt emotions as a means for achieving a desired emotional display. The literature has also mainly examined positive displays, yet there are many situations that call for the display of negative emotions. To advance theory and research, we draw from theory on central principles of approach/avoidance motivation to understand why an individual would choose a given emotional display method, as well as the extent to which a given method is beneficial versus harmful to individuals. In doing so, we identify the valence of the emotion being displayed as a critical factor influencing the benefits and detriments of emotional display methods. Results of a 3‐week experience‐sampling study of 218 employees revealed that mood was associated with the natural display of positive emotion, promotion focus was associated with deep acting, and prevention focus was associated with surface acting. In positive display contexts, displaying emotion naturally was most beneficial (in terms of effects on emotional exhaustion, job satisfaction, and work withdrawal), whereas surface acting was most detrimental. In negative contexts, this relationship pattern was reversed.